INOVASI PELAYANAN ADMINISTRASI KEPENDUDUKAN ( Studi Kasus Pada Pelayanan Lempeng Gapit di Dinas Kependudukan dan Pencatatan Sipil Kota Madiun) - Wyke Santika Dewi (Universitas Sultan Ageng Tirtayasa, 2020)
The death certificate is an important document for individuals and countries because ownership of a death certificate can be used for insurance, retirement, inheritance management and the determination of a widow or widower in the National Identity Card. For Countries, deeds are also important as the statistical. The lack of public awareness in Madiun regarding the ownership of a death certificate has prompted the Madiun City government to create an innovative death certificate service, namely “Lempeng Gapit”, or better known as “One-day Service for Managing Population Document and Civil Registration Officers who send it and get there”. This research aims to explain about the attributes or characteristics of “Lempeng Gapit” innovation in Madiun City using the Rogers 2003 theory which there are 5 dimensions, namely Relative Advantage, Suitability, Complexity, Possibility to Try, and Ease of Observation. The type of research is a qualitative descriptive research method. Sources of data in this tudy consisted of primary data sources, namely several informants and secondary data sources in the form of documents related to research. The data collection technique is structured documentation interviews. The data analysis technique is an interactive data analysis consisting of data reduction, data presentation, conclusions, and verification. In maintaining the validity of the research data, this study used source triangulation technique and triangulation methods. The results showed that the existence of “Lempeng Gapit” innovation made it easier for people to obtain a death certificate and “Lempeng Gapit” innovation in Madiun City can efficiently time, energy and costs in providing services of population administration.